Potencial do cnidário Protopalythoa variabilis dos recifes coralíneos Brasileiros como fonte de enzimas e toxinas polipeptídicas para aplicação em biotecnologia. - Morlighem, Jean Etienne Romaric Léandre (2018)
Although largely unexplored, the oceans, with its unique ecosystems inhabited by a large variety of species, including a significant number of venomous animals, is collectively recognized as a potential unexplored reservoir of enzymes and toxins candidates for high-value in industrial, biotech or biomedical applications. In the present study, a marine zoantharian of the species Protopalythoa variabilis, which inhabits the Brazilian reefs, was investigated in relation to its content of biologically and pharmacologically active peptides of venom and enzymes of biotechnological interest. For this purpose, after obtaining the holo-transcritome of P. variabilis by RNA-Seq, the polyadenylated transcripts were identified and characterized by bioinformatics methods. The putative toxins were investigated by similarity, by comparison of the contigs against known proteic sequences of animal toxins; then such predicted sequences were validated by the presence of characteristic structural domains, as well as by similarity inference with families of toxins. To identify the catalytic activities expressed in the holo-transcriptome, all transcripts of the holobiont were initially annotated against four databases of proteic sequences from eukaryotic and prokaryotic organisms, followed by search of gene ontology, enzymatic activities and metabolic pathways. In addition, multifunctional enzymes and enzymes with partially characterized activities were predicted using scripts specifically written for this purpose. As a whole, the holo-transcriptome analysis revealed 12 toxin families, including a neurotoxin only described in anthozoan, and two new toxin families which were for the first time described in a cnidarian species: a three-finger neurotoxin (3FTx), and a helophensin-like peptide active on membranes. Concerning the enzymatic potential of this cnidarian, 771 enzymatic activities, such as used in the treatment of metabolic diseases or in the preparation of fine chemicals, were found in addition to at least thirteen enzymes characterized as multifunctional and 694 sequences with partially characterized activities distributed in 23 sub-subclasses. This study thus demonstrates that P. variabilis contains several toxin precursors with unique sequences and hundreds of potential enzymatic activities, which can be purified or cloned for application in diverse fields of the industrial and pharmaceutical biotechnology.